The Basic Principle of The Man to Islamic View - Musyarif Musyarif; Ahdar Ahdar (LPPM IAIN Parepare, 2019)
The concept of man according to the Qur'an is understood by paying attention to the words that each man is pointing at the meaning of Bechar, insane, and al - nas. God used the concept of Bechar in the Qur'an 37 times, the concept of Bechar is always connected to the biological properties of human origin such as clay or dry plate, the human eating and drinking, Bechar is just a creature being) static like animals. The word insan is mentioned in the Qur'an as much as 65 times. The concept of insane is always connected to the insane concept of psychological or spiritual nature of man as a creature who thinks, bear the mandate and given knowledge ( al - Ahzab : 72 ), human beings are becoming (becoming) and continues to move forward towards perfection. Said Al - Nas called 240 times, the concept of al - Nas refer to all human beings are social or collective.